11.27 Late onset multiple sclerosis in north wales. Issue 12 (14th November 2019) - Karthikeayan, Venkatraman; Copeland, Yvonne; Fearn, Catriona; Whittam, Daniel; Elsone, Liene; Huda, Saif; Jacob, Anu
Abstract : Introduction: MS patients who have their first symptom onset after 50 years of age are defined as Late onset Multiple Sclerosis (LOMS). Our study analyses the clinical profile of patients with LOMS in North Wales region of United Kingdom Methods and materials: A retrospective medical record review of all patients attending regional MS clinic in North Wales, based at Glan Clwyd Hospital (2007–2018) was done. Results: Of 648 patients with MS, 60 (9.2%) had LOMS. Mean age at onset was 55.3 years and the M: F ratio was 1:1.85. 63% and 28% of LOMS were progressive and relapsing types respectively. At a mean of 7.8 years follow up, 31% of relapsing patients converted to SPMS. Majority of LOMS presented with gait difficulties-67% (97% in Progressive MS and 23% in relapsing).Only 15% of the relapsing MS patients were eligible or chose DMT. Conclusions: LOMS forms at least 9% of this MS cohort with majority presenting with a progressive course at diagnosis. The high proportion of LOMS in this cohort may reflect, delayed reporting of symptoms or slower access to care.